A CLINICAL STUDY TO EVALUATE THE EFFICACY OF SELECTED TRADITIONAL HAIR PACK FOR DANDRUFF - Pramodani, M.P.N.; Wickramarachchi, W.J. (International Journal of Research -GRANTHAALAYAH, 2017)
Darunaka is a disease concerned to hair root which can be correlate with Dandruff, which is the most common cause for hair loss. It is more of a social problem and affects aesthetic value as a person with Dandruff is quite likely to feel down on the social ring. Acharya Sushruta has mentioned Darunaka under Kshudraroga’s with symptoms like rukshata, kandu, twak sphutana etc. Dandruff can occur due to air pollution, water pollution, changed life style, irregular daily regimen, poor hygiene and immune system, sweating, mental stress etc which can lead to several bacterial and fungal infections. It is a common scalp disorder affecting almost half of the population at the pre-pubertal age and of any gender and ethnicity. No population in any geographical region would have passed through freely without being affected by dandruff at some stage in their life. Shiroabhyanga, Nasya, Shirodhara , Shirobasti,Shirolepa and Siravyadha is the line of treatment for Darunaka in the classics. In traditional medicine paste of leaves of Elaeocarpus serratus and Psidium guajava are using for thousand years as a home remedy for dandruff in Sri Lanka .In spite of the present medical solutions Dandruff relapses quite often. A permanent and holistic solution is the need of the hour. Hence, this work is intended to study the efficacy of Elaeocarpus serratus and Psidium guajava leaves paste for dandruff. Thirty patients were selected; advised to apply the paste covering whole scalp area for one hour and rinse it, for a period of one month every alternative day. Signs and symptoms were assessed by using grading system and observed the significant reduction of symptoms. Considering the total treatment assessment more than 40% patients gain complete remission and 30% got marked improvement. No adverse reaction reported in this study period. It is concluded that Elaeocarpus serratus and Psidium guajava leaves paste is very beneficial to manage Dandruff.